Denture stomatitis: Ethiopathogenesis and therapeutic approach - Đorđević Milica Č; Obradović Radmila R.; Miljković Milan N.; Milošević Marija R.; Sekulić Miona Lj (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Introduction: Denture stomatitis is the most common inflammatory reaction that occurs in people who wear dentures, localized mostly in the palatal mucosa. Etiophatogenesis of inflammation is multifactorial and complex. Infection by yeast of the genus Candida, mainly Candida albicans, poor oral hygiene and long-term wearing of dentures are the most important etiological factors. Factors that may contribute to the development of inflammatory reactions are some general factors, such as smoking, use of different drugs, and systemic diseases such as diabetes mellitus. As the inflammation usually goes without any symptoms and has high prevalence among denture wearers, it is desirable for patients to schedule regular examinations to obtain diagnosis early and to receive adequate therapy. Conclusion. The manuscript presents the etiopathogenesis of denture stomatitis and usual therapeutic procedures that are carried out during treatment.